Key recommendations and research priorities of the 2021 AMAP human health assessment - Cheryl Khoury; Pál Weihe (International Journal of Circumpolar Health)
Over the last three decades, the Arctic Monitoring and Assessment Programme has published five human health assessments. These assessments have summarised the current state of the science regarding environmental contaminants and human health in the Arctic. The 2021 Human Health Assessment Report had a particular focus on dietary transitions, in addition to human biomonitoring levels and trends, health effects, risk assessment methodologies, risk communication and multi-disciplinary approaches to contaminants research. The recommendations and research priorities identified in the latest assessment are summarised here to assist decision- and policy-makers in understanding and addressing the impacts of contaminants on human populations in the Arctic.